New evidence on technological acceptance model in preschool education: Linking project-based learning (PBL), mental health, and semi-immersive virtual reality with learning performance - Zang, Juanjuan; Kim, Youngsoon; Dong, Jihe (Frontiers in Public Health, 2022)
In the Chinese institutes of education, the appropriate resources are not provided for the students to improve their learning performance with the help of effective and reliable teachers and other resources. This study aimed to identify the important role of project-based learning, semi-immersive virtual reality, and mental health in learning performance. Further, 800 questionnaires were distributed to the different respondents of the schools and colleges in China to collect the data to check the relationship between different hypotheses of the study, and 290 questionnaires were considered for this study. Moreover, the scope of the study is important for the teaching institutes in China to improve the performance of the students by providing them with the right opportunities at the right time for getting the right output from the students. Additionally, this study provides significant practical implications related to the relationship between project-based learning and the learning performance of the students with the help of innovative technology acceptance. Importantly, the results of this study also demonstrate that there is also a critical modeling role of mental health and semi-immersive virtual reality in the relationship between project-based learning and learning performance.